Challenges in emergency departments in teaching hospitals of Mashhad University of Medical Sciences: A qualitative study (Tehran University of Medical Sciences, 2017)
Background: The emergency department is as heart of hospital and is one of the first points of contact for patients with health care system are facing a variety of challenges. This study aimed to explore the challenges of emergency departments in teaching hospitals of Mashhad University of Medical Sciences. Materials and Methods: This study was carried out through a qualitative approach and phenomenology method in 2013 in Mashhad, Iran. Twenty nurses and two emergency medicine specialists were recruited from four teaching hospitals in Mashhad Iran using purposive sampling. Data were collected through semi-structured in-depth interviews. Interviews were transcribed verbatim and analyzed using conventional content analysis approach according to colaizzi  with MAXQDA 3 software.  Results: The results of this study indicated that challenges of emergency department lay in Three main aspects including: "challenges in Human resources"(personal characteristics,  professional characteristics and human resource limitations), "nurseschr('39') dissatisfaction"(less quality hospital hoteling and services for staff, disproportion between the workload and salaries, Lack of support from nurses) and " challenges in human resources management "(Structural challenges, the performance challenges and challenges in human resource management). Each theme included several category and subcategory that explain various aspects of the challenges in emergency department. Conclusion: Human resource limitations, nurseschr('39') dissatisfaction and poor management were the most important challenges. Providing adequate human resources, support of nurses and determination guidelines and process for nursing care can reduce these challenges in hospital emergency departments.